Association between descending pain modulatory system and cognitive impairment in fibromyalgia: A cross-sectional exploratory study - Serrano, Paul Vicuña; Zortea, Maxciel; Alves, Rael Lopes; Beltran, Gerardo; Deliberali, Cibely Bavaresco; Maule, Amanda; Torres, Iraci L. S.; Fregni, Felipe; Caumo, Wolnei (Frontiers in Behavioral Neuroscience, 2022)
Background: The successful regulation of sensory input to the central nervous system depends on the descending pain modulatory system (DPMS). For the effective regulation of sensory input to the central nervous system and behavioral responses to pain, the DPMS is required. Its connection to fibromyalgia (FM)-related cognitive dysfunction has not yet been investigated. Therefore, this study tested whether measures of verbal fluency, sustained attention, and short-term and working memory could distinguish FM patients from healthy controls (HC). Additionally, it investigated, using a standardized paradigm, the link between cognitive ability and the function of the DPMS in responders and non-responders to the conditioned pain modulation test (CPM-test). Methods: We enrolled 21 HC women and 69 F.M. patients, all of whom ranged in age from 30 to 65. We employed scores from the Trail Making Test (TMTB-A) (sustained and divided attention), the Controlled Oral Word Association Test (COWAT) (orthographic and semantic fluency), and the Digits subtest of the Wechsler Adult Intelligence Scale (WAIS-III) as dependent variables. Results: A generalized linear model (GLM) adjusted by educational level revealed significantly lower scores in F.M. than HC on the Span digits forward, COWAT-orthographic, and TMTB-A. For F.M. patients, multilevel MANCOVA revealed that the cognitive performance of non-responders compared to responders to CPM-test showed lower adjusted scores in Span digits forward (Partial-η2=0.358, P=0.001), Span digits backward (Partial-η2=0.358, P=0.001), COWAT-orthographic (Partial-η2=0.551, P=0.001), COWAR-semantic (Partial-η2=0.355, P=0.001), and TMTB-A (Partial-η2=0.360, P=0.001). The association between the cognitive tests and the DPMS is moderated by the serum level of brain-derived neurotrophic factor (BDNF). Additionally, these cognitive assessments had a positive correlation with antidepressant use and pain threshold. The cognitive assessments, on the other hand, were conversely associated with a life of quality Conclusion: Based on these findings, it can be shown that H.C. performed substantially better on cognitive exams than F.M. did. They demonstrated a link between clinical complaints about attention and memory and decreased DPMS effectiveness. Additionally, they demonstrated that the BDNF is a moderating element in a potential relationship between the severity of cognitive impairment and DPMS dysfunction.